Hydroponic Business Diversification: Health Detox Drinks In Improving The Economy And Food Security Of Urban Communities In South Meruya - Zamzami, Annisa Hakim; Asih, Daru; Melzatia, Shinta; Putri, Febry Kurnia; Saputra, Ahmad Reza (Jurnal Abdi Masyarakat (JAM), 2024)
One way to reduce greenhouse gas emissions is by reforestation. Reforestation that can provide benefits for South Meruya residents who have limited land can use the Hydroponic method to grow crops. In order for the buying and selling power of hydroponic vegetables to increase, it is necessary to develop the business by increasing the types of products derived from hydroponic harvests, namely health detox drinks, to improve the economy and family food security. This activity is designed holistically to introduce the public to the concept of the importance of business diversification to find product ideas that can be developed from existing resources, calculate cost and selling prices, create attractive product packaging with halal guarantees, and market products online through media. social and marketplace. Potential that can be developed by partners includes the willingness of South Meruya PKK women, internet networks, awareness of entrepreneurship, increased demand for healthy food and drinks, especially hydroponic vegetables and derivative products, health detox drinks. In the end, this activity is expected to improve the economy of the urban communities targeted by the activity.